LITERATURE REVIEW : REGULASI DAN PENGAWASAN PENGOBATAN TRADISIONAL: ANALISIS IMPLEMENTASI UU KESEHATAN DAN STANDAR KOMPETENSI TENAGA TRADISIONAL - Nani Yuniar; Rastika Dwiyanti Liaran; Nur Tri Septianingsih; Nurhikmadani; Rencong Pandelaki; Mutiara Nur Islami; Nila Hildayani; Putri Revina (JURNAL ILMIAH RESEARCH STUDENT, 2026)
Traditional medicine is a health practice based on hereditary customs that has been legally recognized in Indonesia. It is regulated under Law No. 36 of 2009 on Health, Government Regulation No. 103 of 2014, and Health Law No. 17 of 2023, which governs traditional medicine as a legitimate health practice in Indonesia. To ensure the safety and quality of services, the Health Law establishes licensing and competency standards for Traditional Health Practitioners, as well as strict regulations regarding the practice and use of traditional medicine. The method used in this study is a literature review from a single electronic database, namely Google Scholar. This study is based on the analysis of 5,490 clinical articles and research studies published between 2021 and 2025. From the four articles used in this literature review, all four indicate a significant relationship regarding Regulation and Supervision of Traditional Medicine: Analysis of the Implementation of the Health Law and Competency Standards for Traditional Practitioners.